Examining the Level of Readiness of Tehran Municipality to Implement Knowledge Management - Rahmani, Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2022)
Purpose: Today, knowledge management is considered one of the main components of the success of organizations. The purpose of this research is to investigate the level of readiness of Tehran municipality to implement knowledge management in that organization. Research method: The current research is applied in terms of purpose and survey-analytical in terms of method. The current research has measured the readiness of the organization based on 7 components of leadership, knowledge management, process, people, technology, knowledge processes, learning and innovation and the results of knowledge management. In order to achieve the objectives of the research, in addition to theoretical studies and research literature review, data was collected through the existing knowledge management checklist of the Asian Productivity Organization, and this checklist was completed by 44 experts working in the municipality of Tehran and answered each of the questions. Answered. Data analysis was done through descriptive statistics. Findings: The results showed that the level of readiness of Tehran municipality to implement knowledge management is at the development level and this shows that the group has taken regular plans to implement knowledge management in the organization. Conclusion: The results indicated that the status of the organization is developing and activities for the implementation of knowledge management have been carried out in the organization and there are areas for the advancement of knowledge management in the organization. The state of development means that knowledge management has been comprehensively implemented in the organization, but it has not yet reached the maturity level. Tehran municipality has invested a lot in the technology sector and has a favorable situation in this field. But because the implementation of knowledge management in the organization is developing, it is natural that the results of organizational knowledge management are not at a suitable level, and knowledge management has not yet been implemented at a general level, and it cannot be said that it has had results for the organization.